2021
DOI: 10.1016/j.jiac.2020.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Factors significantly associated with COVID-19 severity in symptomatic patients: A retrospective single-center study

Abstract: Introduction The severity of coronavirus disease (COVID-19) in Japanese patients is unreported. We retrospectively examined significant factors associated with disease severity in symptomatic COVID-19 patients (COVID-Pts) admitted to our institution between February 20 and April 30, 2020. Methods All patients were diagnosed based on the genetic detection of severe acute respiratory syndrome coronavirus 2. Information on the initial symptoms, laboratory data, and compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Three studies were prospective [ 29 , 41 , 52 ], 51 retrospective [ 20 28 , 30 34 , 36 39 , 42 46 , 48 51 , 53 , 54 , 57 60 , 62 , 63 , 65 , 66 , 69 76 , 78 , 80 , 81 , 83 86 ], while 13 did not specifically declare the study design [ 23 , 35 , 40 , 47 , 55 , 56 , 61 , 64 , 67 , 68 , 77 , 79 , 82 ]. Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were prospective [ 29 , 41 , 52 ], 51 retrospective [ 20 28 , 30 34 , 36 39 , 42 46 , 48 51 , 53 , 54 , 57 60 , 62 , 63 , 65 , 66 , 69 76 , 78 , 80 , 81 , 83 86 ], while 13 did not specifically declare the study design [ 23 , 35 , 40 , 47 , 55 , 56 , 61 , 64 , 67 , 68 , 77 , 79 , 82 ]. Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 ...…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 , 65 67 , 86 ]. Endpoints included disease severity based on current clinical guidelines (31 studies, 46%) [ 22 , 24 , 28 , 32 , 33 , 35 , 36 , 38 , 39 , 44 47 , 49 52 , 54 , 56 , 58 , 64 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 83 ], survival (19 studies, 28%) [ 20 , 23 , 26 , 30 , 31 , 34 , 42 , 53 , 59 – 62 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…Several observational studies ( An et al, 2020 ; Batty et al, 2021 ; Cavallaro et al, 2020 ; Collaborative, 2021 ; Cummins et al, 2021 ; Fond et al, 2020 ; Giannoglou et al, 2020 ; Hirashima et al, 2021 ; Jeon et al, 2020 ; Lee et al, 2020a ; Lee et al, 2020b ; McKeigue et al, 2020 ; Nemani et al, January 2021 in JAMA psychiatry; Wang et al, 2020 ; Yang et al, 2020 ; Yanover et al, 2020 ) investigated whether people with mental disorders have poorer COVID-19 outcomes or not, thus we have decided to conduct this meta-analysis that aims to investigate the relationship between pre diagnosed psychiatric illness and COVID-19 mortality and severity suggesting that people with mental disorders might have worse outcome of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A similar retrospective study in Japan by Hirashima, T., et al reported a significant correlation between hypertension, older age, diabetes, and disease severity. The critical group exhibited higher levels of CRP than the moderate group [ 185 ]. Consistently, a Spanish retrospective study, showed that IL-6, ferritin, D-dimer, and CRP levels were higher as disease severity increased [ 186 ].…”
Section: Impact Of Obesity and T2d In Covid-19 Patientsmentioning
confidence: 99%
“…By extracting clinical summarized data, various studies showed significant evidence of a systemic reduction in T-cell populations (lymphocytopenia) in obese/T2D patients as COVID-19 progressed [ 134 , 155 , 156 , 158 , 162 , 163 , 164 , 170 ]. Importantly, patients hospitalized with underlying conditions presented worse lymphocytopenia than those who did not report comorbidities [ 178 , 185 , 186 , 187 , 189 ]. Based on this information, the majority of the researchers have proposed that lymphocytopenia could potentially be used as an indicator of COVID-19 severity [ 190 , 191 , 192 ].…”
Section: Impact Of Obesity and T2d In Covid-19 Patientsmentioning
confidence: 99%